Men’s reactions to gender inequality in the workplace: From relative deprivation on behalf of women to collective action - Mazzuca, Silvia; Moscatelli, Silvia; Menegatti, Michela; Rubini, Monica (Frontiers in Psychology, 2022)
Over recent years, the role of men as women’s allies in the struggle for gender equality has become increasingly important. Previous research has shown that often men do not fight gender inequalities as they fail to recognize the severity of discrimination against women (e.g., in hiring). In this study (N = 427), we examined whether men who experienced relative deprivation on behalf of women – a form of relative deprivation that stems from the awareness that women hold a less privileged position in society – were more motivated to engage in collective action to support gender equality in the workplace. The findings showed that men’s feelings of deprivation on behalf of women were associated with a greater willingness to engage in collective action for gender equality. This relationship was sequentially mediated by two emotional reactions related to deprivation – increased guilt about gender inequalities and decreased fear of a potential backlash – and the moral conviction of acting for gender equality. These results suggest that men’s awareness of gender inequality at work is an important antecedent to their acting in solidarity with women and that emotions and moral conviction are two psychological processes that turn cognition into behavior. Action to reduce gender inequalities should make men more sensitive to seeing that they hold a privileged position in society and to recognizing the pervasive and harmful nature of women’s deprivation.